Mechanical characteristics of non-saturated tailings and dam stability. Issue 8 (17th November 2017) - Zhang, Chao; Liu, Haiming; Yang, Chunhe; Wu, Shangwei
Abstract: The failure of tailings dams has repeatedly occurred in China, which seriously threats eco-environment and social economy. The mechanical properties of non-saturated tailings are a matter of great concern, yet remain poorly understood. In this paper, engineering properties of non-saturated tailings are measured and complemented by analysis and interpretation from multiple perspectives. The results indicate that the soil–water characteristic curve, influenced by dry density, can be described with an appropriate model through parameter analysis. In order to calculate the stability of a typical tailings slope under different conditions, a new approach that considers the contribution of matric suction is elaborated in a sound theoretical framework.